Pemahaman Pendidikan Nonformal - Devina Wliyana; Sofino Sofino; Ririn Gusti (Jurnal Pendidikan Sepanjang Hayat, 2020)
The purpose of this research is to describe understanding by new students of nonformal education at Bengkulu University about nonformal education. As for the scope studied in this research was students understanding about the scope nonformal education which consist of understanding , characteristics , goals , roles, programs , institution and education facilities. Furthermore, reviewing the understanding of students at bengkulu university about the graduate competence and employment opportunity of S1 non formal education.  The design of this research was descriptive quantitatif research, this method carried out with the main goal to make an idea of situation objectively, the respondents of this research were new students of nonformal education study program at Bengkulu University. The result and discussion of this research that understanding of new students of nonformal study program at Bengkulu University about scope of informal education was high enough with percentage 69.4%, understanding about the graduate competence of S1 non formal education was sufficient with percentage 51% and understanding about employment opportunity of S1  non formal education was highwith percentage 67.5% Key words : understanding, students, nonformal education